(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
The article delves into Ibn Rushd’s perspectives on the notions of freedom and necessity, as a prominent figure within the Eastern Peripatetic movement. His stance is elucidated through his rejection of the prevailing notions held by his peers. Within the medieval philosophical landscape, the discourse surrounding freedom and necessity often revolved around reconciling religious and philosophical ideologies. The article particularly highlights discussions on fate and volition.